Wh-Questions Constructed By The Structure II Students of The English Department of Widya Mandala Catholic University Surabaya - Magdalena Indriani Jasi (Magister Scientiae, 2013)
A functional syllabus focuses on fluency which may lead to the less attention on grammatical rules. It accounts for grammar errors in producing sentences including in asking questions. This study explored Wh-question errors by using the Surface Strategy Taxonomy. The results show that the students’ ability in constructing Wh-questions in Simple Present Tense, Simple Past Tense and Simple Future Tense was insufficient. The most frequent error in Simple Present Tense was the Wh word; the error consists of 96 errors in misformation; for the Simple Past Tense was verb, the errors consist of: 6 errors in omissions, 59 errors in addition, 64 errors in misformation and 3 errors in misordering, for the Simple Future Tense was the subject, the errors consists of: 6 errors in omission, 2 errors in misformation and 135 errors in misordering.